PEMAHAMAN FENOMENOLOGI KEMAJUAN TEKNOLOGI INFORMASI TERHADAP PERKEMBANGAN SISTEM INFORMASI AKUNTANSI (Studi Kasus Pada Mahasiswa Akuntansi Fakultas Ekonomi Universitas Kanjuruhan Malang) - Syarifatul Ummah, Eka Aulia (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2014)
Advances in information technology continues to increase will impact the accounting knowledge. One is the development of accounting information systems. A concrete example of accounting information systems development due to advances in information technology is processing data from a manual system to a computerized system . So this will result in a quality accounting information . This study aims to determine the student's understanding of Accounting class of 2010 and 2011, the Faculty of Economics, University of Kanjuruhan Malang the phenomenon of information technology advances in the development of accounting information systems with the phenomenological paradigm. This study used qualitative methods of data analysis technique consists of data reduction (the phenomenological reduction, eidetic reduction and reduction transcedental), after the presentation of the data and conclusions withdrawal . The results of this study indicate that the understanding of the phenomenon of accounting students will progress in the development of information technology accounting information system is good enough because their statement is supported by several previous investigators and in accordance with the theory applies. For further research it is expected to add to and expand the research object not just to one place but could be fixed by using a phenomenological paradigm.